Mechanical behavior of materials : engineering methods for deformation, fracture, and fatigue - Dowling, Norman E. , 1945- (Pearson, 2013)
"Mechanical Behavior of Materials, 4/e introduces the spectrum of mechanical behavior of materials, emphasizing practical engineering methods for testing structural materials to obtain their properties, and predicting their strength and life when used for machines, vehicles, and structures. With its logical treatment and ready-to-use format, it is ideal for upper-level undergraduate students who have completed elementary mechanics of materials courses." -- Publisher's website